Natural Disasters, Corpses and the Risk of Infectious Diseases. Issue 5 (2005) - Conly, JM; Johnston, BL
Abstract : The recent occurrence of the category 4 Hurricane Katrina devastated the United States? Gulf Coast. The hurricane caused widespread destruction and flooding, and left hundreds of thousands of people homeless. The mounting death toll was reported at almost 300 deaths as of September 8, 2005 (1, 2). The unfolding events and high death toll have left an unusual situation in which there are many decomposing corpses either lying on the streets or floating in the flood waters. The presence of these corpses in open settings, such as in public places and in the water that has inundated much of the city of New Orleans, naturally raises concerns about the occurrence of infectious disease epidemics (3). In the aftermath of large natural disasters, instinctive uncertainties arise among workers and the general population with respect to the appropriate handling and disposal of dead bodies and human remains. Given the recent occurrence of Hurricane Katrina as a large natural disaster and the unprecedented setting of the numerous corpses requiring disposal, it was considered timely to review the infectious disease risks associated with the handling of dead bodies.